Investigation on the effect of the rear under-run protective device of heavy vehicle using finite element simulation - Yusoff, Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In rear-end collisions with other vehicles, such as trucks; the crashworthiness of the rear under-run protective device of the truck directly affects the safety of the occupants of the vehicle. Rear-end crashes between cars and trucks result in a significant number of fatalities and serious injuries, which makes them a major public safety problem. This research paper is to study the effect of the collision of rear under-run protective device of truck and its damage behavior when it is collide with cylinder. RUPD beam and cylinder collisions will investigate using the finite element method and will be simulated in ABAQUS/CAE software. The entire structure of rear under-run protective device has been designed in ABAQUS/CAE according to the actual parameters on the real rear under-run protective device beam. Steel material is applied for the whole RUPD beam structure and mass of cylinder is 115 Kg. The predefined field feature was used to apply the velocity to the cylinder-shaped impactor with 80 km/h and the load for cylinder is 5000N. According to the data acquired for force against time, the force reaches a maximum value of 580kN and with a displacement value of 100.052mm at time 0.02, the beam displacement value also reached its maximum level. The data reveals that the amount of energy absorbed increased significantly from time 0.006 to 0.02, peaking at time 0.02, when it reached a value of 2831.067 J. The RUPD beam's ability to absorb more energy demonstrates that its design is more crashworthy and capable of providing a good performance when colliding with the cylinder.